2021
DOI: 10.32799/ijih.v16i2.33903
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Women Voicing Experiences of HIV Stigma and Criminalization Through Art

Abstract: Indigenous women living with HIV are disproportionately affected by the criminalization of HIV nondisclosure. The purpose of this paper is to better understand how the criminalization of HIV nondisclosure shapes the lived experiences of HIV-related stigma, disclosure, and health service among cis and transgender Indigenous women living with HIV (IWLWH). This study was developed based on a community roundtable on HIV criminalization with engagement of legal experts, HIV service organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The interplay between gender-based inequities and laws criminalizing HIV non-disclosure constrains the sexual rights of women living with HIV. 32 Consistent with previous work, 44,49 our analysis showed that HIV non-disclosure case law may undermine the sexual agency of women living with HIV, representing a barrier to the formation of new sexual partnerships, and precluding women from realizing sexual agency and empowerment in the era of U = U. 2 Similarly, focus groups and in-depth interviews among women living with HIV in Ontario identified the law as a barrier to fully engaging in sexual relationships, regardless of whether a woman had an undetectable viral load or intended to use condoms.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The interplay between gender-based inequities and laws criminalizing HIV non-disclosure constrains the sexual rights of women living with HIV. 32 Consistent with previous work, 44,49 our analysis showed that HIV non-disclosure case law may undermine the sexual agency of women living with HIV, representing a barrier to the formation of new sexual partnerships, and precluding women from realizing sexual agency and empowerment in the era of U = U. 2 Similarly, focus groups and in-depth interviews among women living with HIV in Ontario identified the law as a barrier to fully engaging in sexual relationships, regardless of whether a woman had an undetectable viral load or intended to use condoms.…”
Section: Discussionsupporting
confidence: 89%
“…35 Photo-voice workshops among 17 Indigenous women living with HIV in BC highlighted the intersection between HIV criminalization and colonial violence in shaping experiences of disclosure, violence and stigma. 49 These findings illuminate a need for culturally sensitive, traumaaware services tailored to marginalized and racialized groups. They also speak to the importance of an intersectional approach to structural stigma to understand how HIV non-disclosure case law is enacted and experienced differentially in ways that exacerbate pre-existing social inequities among women living with HIV.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Such critiques of molecular surveillance are grounded in longstanding critiques against the racist practices of medicine and public health, which view the bodies of people living with HIV solely as objects of risk and study, not subjects deserving of rights and decision-making [32 ▪ ]. In Canada, qualitative research with Indigenous women living with HIV has proposed the experience of over-surveillance by health professionals, police, and the law, as a form of ‘colonial surveillance and racism’ [39 ▪ ]. Critical public health scholars in the area have called for research into the implications of increased surveillance, and for all approaches to be grounded in human rights and racial justice [20 ▪ ].…”
Section: Criminalization and Molecular Surveillancementioning
confidence: 99%